Friendship and dialogue - Carmichael, E (Pennsylvania State University Press, 2017)
This article explores links between Christian love, friendship, and dialogue in the context of inter-faith encounter. It discusses Christian love, agapē, as having the nature of open friendship-love, which motivates dialogue. A practical example of dialogue is presented: a Three Faiths Encounter program that has succeeded over the past three decades to bring about deeper understanding, overcome fears and barriers, and create friendship between Jewish, Christian and Muslim participants. Strengths and weaknesses are discussed, and some further examples of initiatives that express and create friendship are introduced.